2016
DOI: 10.1002/hipo.22580
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic stress exacerbation in hippocampal neurons: Evidence favoring the dual‐hit hypothesis of neurodegeneration

Abstract: The dual hit hypothesis of neurodegeneration states that severe stress sensitizes vulnerable cells to subsequent challenges so that the two hits are synergistic in their toxic effects. Although the hippocampus is vulnerable to a number of neurodegenerative disorders, there are no models of synergistic cell death in hippocampal neurons in response to combined proteotoxic and oxidative stressors, the two major characteristics of these diseases. Therefore, we developed a relatively high-throughput dual hit model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 102 publications
1
12
1
Order By: Relevance
“…NAC has been shown to protect primary neurons and neuroblastoma cells against proteasome inhibition Jiang et al, 2013;Posimo et al, 2013;Heinemann et al, 2016). In contrast to our previous studies on neuroblastoma cells (Jiang et al, 2013), NAC did not preserve Hsp70 protein levels in primary astrocytes.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…NAC has been shown to protect primary neurons and neuroblastoma cells against proteasome inhibition Jiang et al, 2013;Posimo et al, 2013;Heinemann et al, 2016). In contrast to our previous studies on neuroblastoma cells (Jiang et al, 2013), NAC did not preserve Hsp70 protein levels in primary astrocytes.…”
Section: Discussioncontrasting
confidence: 99%
“…Total GSH levels were measured by In-Cell Western analyses and expressed as a fraction of Hoechst-stained nuclei in the same well to control for differences in cell density. This GSH In-Cell Western assay has been validated in previous studies, in which the signal for GSH was successfully decreased with buthionine sulfoximine and increased with NAC (Leak et al, 2008;Unnithan et al, 2012;Posimo et al, 2013;Titler et al, 2013;Gleixner et al, 2016;Heinemann et al, 2016). Reduced GSH levels were measured by the luminescent GSH-Glo assay according to the manufacturer's instructions (cat.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous report showed that neurons respond to dual hits of high concentrations of paraquat with additive cell loss (Heinemann et al, 2016), suggesting that neurons do not develop stress tolerance in response to severe oxidative toxicity. However, there are many other types of oxidative stimuli, including hydrogen peroxide.…”
Section: Resultsmentioning
confidence: 99%